Cognitive-Behavioral Therapy for pain and insomnia in adults: Review of clinical trials (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The aim of the study was to identify the effects of Cognitive Behavioral Therapy for insomnia (CBT-I) and pain (CBT-CP) applied to adults with chronic pain and insomnia, from a literature review of studies published from 2005 to 2015. Through a PubMed search using the terms “psychology OR psychotherapy OR cognitive behavior therapy AND insomnia OR sleep AND pain", ten studies were selected; seven compared the efficacy of CBT-I with other treatments in the control condition, and three evaluated the efficacy of CBT-I and CBTCP, applied jointly or separately. The CBT-I + CBT-CP and CBT-I showed more comprehensive results compared to the other treatments. However, statistically significant reduction in pain intensity was observed in only one study. Methodological divergences and the small number of studies made it impossible to compare the results, and the effects of joint and isolated application of the treatment components for insomnia and pain could not be clarified.
Keywords: chronic pain; insomnia; cognitive-behavioral therapy; effectiveness